Mobile phone based telemedicine service for rural Bangladesh: ECG - Busra, Umme Sayma; Rahman, Mohammad Zahidur (16th Int'l Conf. Computer and Information Technology, 2014)
Cardiovascular diseases such as; heart attack (coronary thrombosis, myocardial infarction), hypertension, stroke, coronary artery disease (CAD), congestive heart failure, peripheral artery disease (PAD) and diabetes create a new concern worldwide due to its harmness. In Bangladesh where majority live in rural areas that lack specialist care, we envision the need for much larger Internet-based telemedicine systems that would enable a large pool of doctors and hospitals to collectively provide healthcare services to entire populations. We propose a scalable, Internet-based architecture for telemedicine (ECG) to integrating multiple hospitals and mobile medical specialists focusing the rural health centers. This system based on the push model. For the necessity of the research at first we conduct a short survey among different health professional to justify the study more effectively.